PENGARUH JUMLAH NASABAH PEMBIAYAAN MURABAHAH TERHADAP PROFIT PERBANKAN SYARIAH (Studi Kasus Bank X Syariah Capem A Periode 2013-2016) - febi febi; Syamsul Rizal; Ade Fadillah FW Pospos; Khairunnisak Khairunnisak (Fakultas Ekonomi dan Bisnis Islam IAIN Langsa, 2019)
Bank Syariah is a bank stressing on the principles of sharia which is the main foundation in its operation both in the direction of its fund and also in the channeling of its fund (in sharia banking channeling of fund commonly called with financing). Financing is a function of the bank in carrying out the function of the use of funds. Sharia banking concerns an syariah bank and sharia business, covering company, business activity, way and process in conducting its business activity. Murabahah financing is a financing contract of an item by confirming its purchase price to the buyer and the buyer pays it twiceas profit as agreed upon by both. Profit is the ability of management to earn lucome. Profit consists of gross profit, operating profit, and net income. The formulation of the problem in this research is whether the number of customers financing have an effect on the profit of sharia banking. The purpose of research is to determine the effect of murabahah financing customers on the profit of sharia banking. Analytical techniques in this study using quantitative analysis using primary data sources and secondary data with simple regression analysis with SPSS 20 program. The population in this study is all customers in Bank x Sharia A which cousists of customers 4.984 customers, while the sample in this study is number of murabahah customers which is 1,928 customers. Technique of collecting data used documentation method, observation, interview and library method. The results showed that the number of murabahah financing customers had a significant effect with the 0.05 with the sig 0.025 on the profit of sharia banking.